2018
DOI: 10.3389/fgene.2018.00525
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mendelian Randomization for Identifying Risk Factors for Brain Tumors

Abstract: Gliomas are a group of primary brain tumors, the most common and aggressive subtype of which is glioblastoma. Glioblastoma has a median survival of just 15 months after diagnosis. Only previous exposure to ionizing radiation and particular inherited genetic syndromes are accepted risk factors for glioma; the vast majority of cases are thought to occur spontaneously. Previous observational studies have described associations between several risk factors and glioma, but studies are often conflicting and whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 163 publications
(201 reference statements)
0
13
0
Order By: Relevance
“…Because of the inherent bias, it is not possible to determine the direction of causality between the serum UA level and risk of MS from the above-mentioned case-control studies. The method of MR can be used to clarify the causality of exposure factors in disease etiology (Smith and Ebrahim, 2003;Mokry et al, 2015a;Harroud and Richards, 2018;Howell et al, 2018). In MR analysis, genetic variations such as SNPs will be used as surrogate measures of genetically determined lifetime exposure of the trait of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the inherent bias, it is not possible to determine the direction of causality between the serum UA level and risk of MS from the above-mentioned case-control studies. The method of MR can be used to clarify the causality of exposure factors in disease etiology (Smith and Ebrahim, 2003;Mokry et al, 2015a;Harroud and Richards, 2018;Howell et al, 2018). In MR analysis, genetic variations such as SNPs will be used as surrogate measures of genetically determined lifetime exposure of the trait of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the literature on IVs assumes the first case, whereas some applications, in particular Mendelian randomisation, fall into the second category. As the two are not always clearly distinguished in the MR literature (Thanassoulis and O'Donnell 2009;Thompson 2013, 2015;Howell et al 2018), we feel it is important to highlight and discuss the differences here.…”
Section: Two Types Of Instrumental Variablesmentioning
confidence: 95%
“…In another branch of causal discovery, Mendelian randomization (MR) uses genetic variants, such as single-nucleotide polymorphisms (SNPs), that are robustly associated with an exposure as proxies for the risk factor of interest [ 154 ], therefore eliminating confounding and reverse causation effects between the exposure of interest and outcome. Howell et al (2020) [ 155 ] used MR to assess the causal relationship of associations of 36 reported glioma risk factors obtained from a systematic MEDLINE search on observational epidemiology studies.…”
Section: Network Discovery In Glioblastomamentioning
confidence: 99%